A Systematic Review on Interdisciplinary STEM: Integration of Humanities, Arts, and Social Scientific Issues in Science Learning - Budiman, Budiman; Suwarma, Irma Rahma; Aba, Akbar; Irawan, Hendri (Jurnal Pendidikan MIPA, 2023)
Abstract: The aim is to understand the application and impact of STEM Humanities in science education as an implementation reference. This review systematically explores papers published between 2018-2022 through keyword searches and a snowballing approach on the Scopus database; 16 journal papers were included. The analysis shows that Implementation of Interdisciplinary STEM (STEM Humanities), Interdisciplinary Potential of STEM (Students’ perceptions of the relationship between science and non-science), Impact of Interdisciplinary STEM (STEM Humanities). The collective findings of 16 papers show that STEM interdisciplinarity opportunities to combine learning between science and non-science. Allows students to understand problems that exist in the real world. By grasping real-world issues, students can enhance their problem-solving skills, aligning with the demands of the 21st century. Moreover, interdisciplinary STEM ensures that students with disabilities and people of colour feel comfortable in their learning environment, preventing discrimination against students from diverse backgrounds. Keywords: interdisciplinary stem; stem humanities; problem-solving Abstrak: Artikel ini mengeksplorasi temuan terkait interdisipliner STEM dengan fokus integrasi Humaniora, Seni, dan Sosial Sains (STEM Humanistik). Tujuannya adalah untuk memahami penerapan dan dampak Humanistik STEAM dalam pendidikan sains sebagai referensi implementasi. Tinjauan ini secara sistematis mengeksplorasi makalah yang diterbitkan antara tahun 2018 dan 2022 melalui pencarian kata kunci dan pendekatan snowballing pada database Scopus; 16 makalah jurnal dimasukkan dalam ulasan ini. Analisis menunjukkan bahwa Implementasi Interdisipliner STEM (STEM Humanistik) Potensi Interdisipliner STEM (Persepsi siswa pada hubungan antara sains dan non sains) Dampak Interdisipliner STEM (STEM Humanistik). Temuan kolektif dari 16 makalah menunjukkan bahwa interdisipliner STEM membuka peluang untuk menggabungkan pembelajaran antara sains dengan non sains. Hal tersebut, dapat membuat peserta didik memahami masalah yang ada di dunia nyata. Dengan memahami masalah dunia nyata, peserta didik dapat meningkatkan keterampilan pemecahan masalah yang sesuai dengan keterampilan tuntutan abad 21. Selain itu, interdisipliner STEM memberikan kenyamanan peserta didik disabilitas dan kulit berwarna dalam belajar sehingga tidak terdapat deskriminasi pada siswa dengan latar belakang yang berbeda.  Kata kunci: kemampuan berpikir kreatif matematis, means-ends analysis, pendekatan realistik, kemandirian belajar siswaDOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp571-583